Modeling Nonlinear Acoustooptic Coupling in Fiber Optics Based on Refractive Index Variation due to Local Bending. (18th September 2016) - Castano, Catalina Hurtado; Herrera, Rodrigo Acuna; Torres, Pedro I.
Abstract : A detailed procedure is presented to compute analytically the acoustooptic coupling coefficient between copropagating core and lowest-order cladding modes in tapered fiber optics. Based on the effect of the local bending, the linear and nonlinear variations in the refractive index are modeled. A set of equations and parameters are presented in order to calculate the influence of acoustooptic effect in nonlinear pulse propagation. We will show that as the tapered fiber diameter decreases more energy can be transferred to the cladding and the nonlinear phenomena can compensate the coupling coefficients effects.